Seasonal spatial dynamics of butterfly migration. (18th June 2021) - Chowdhury, Shawan; Zalucki, Myron P.; Amano, Tatsuya; Woodworth, Bradley K.; Venegas‐Li, Ruben; Fuller, Richard A.
Abstract: Understanding the seasonal movements of migratory species underpins ecological studies. Several hundred butterfly species show migratory behaviour, yet the spatial pattern of these migrations is poorly understood. We developed climatic niche models for 405 migratory butterfly species globally to estimate patterns of seasonal movement and the distribution of seasonal habitat suitability. We found strong seasonal variation in habitat suitability for most migratory butterflies with >75% of pixels within their distributions showing seasonal switching in predicted occupancy for 85% of species. The greatest rate of seasonal switching occurred in the tropics. Several species showed extreme range fluctuations between seasons, exceeding 10‐fold for 53 species (13%) and more than 100‐fold for nine species (2%), suggesting that such species may be at elevated extinction risk. Our results can be used to search for the ecological processes that underpin migration in insects, as well as to design conservation interventions for declining migratory insects. Abstract : We developed climatic niche models for 405 migratory butterfly species globally. We found strong seasonal variation in habitat suitability for most species and the greatest rate of seasonal switching occurred in the tropics.